Chromosome evolution in three Brazilian Leptodactylus species (Anura, Leptodactylidae), with phylogenetic considerations - Cruz Campos, Joao Reinaldo [UNESP]; Ananias, Fernando; Brasileiro, Cinthia Aguirre; Yamamoto, Marcos; Baptista Haddad, Celio Fernando [UNESP]; Kasahara, Sanae [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Karyotypic analyses on three species of the Leptodactylus from Brazil showed 2n=24 in L. cf. marmoratus, 2n=23 in Leptodactylus sp. (aff. bokermanni), and 2n=26 in L. hylaedactylus, with distinct numbers of bi and uni-armed chromosomes. Leptodactylus cf. marmoratus presented a variation as regard to the morphology of pair 12. All specimens of L. cf. marmoratus had Ag-NOR in pair 6, confirmed by FISH, but the sample from one of the localities presented additional Ag-NOR, in one of the chromosomes 8. In Leptodactylus sp. (aff. bokermanni) and L. hylaedactylus the chromosome pairs bearing Ag-NOR are 11 and 7, respectively. The C banding patterns are predominantly centromeric, but only in L. marmoratus this heterochromatin appeared very brilliant with DAPI. on the other hand, bright labelling was noticed with CMA(3) in the three species, on the Ag-NOR site. The data obtained here are in accordance with the proposed phylogeny to the genus, and the chromosomal analyses in these Leptodactylus showed that the karyotype evolution was based mainly in centric fusion and pericentric inversion.